Diversity of stink bugs (Pentatomidae) in Chloris distichophylla Lag. (Poaceae) overwintering - Engel, Eduardo; Pasini, Mauricio P. B. (Entomological Communications, 2019)
The objective of this study was to evaluate the diversity and abundance of stink bugs in Chloris distichophylla Lag (Poales: Poaceae) during the soybean and corn off-season. The work was carried out in the municipality of Cruz Alta, Rio Grande do Sul state, over the soybean and corn off-season between 2014 and 2018. 3543 adults were identified into six species: Euschistus heros (Fabricius, 1798), Dichelops furcatus (Fabricius, 1775), Dichelops melacanthus (Dallas, 1851), Edessa meditabunda (Fabricus, 1794), Edessa ruformaginata (De Geer, 1773) and Piezodorus guildinii (Westwood, 1837) (Hemiptera: Pentatomidae). E. heros was the most abundant, followed by D. furcatus. The diameter of the clumps directly affects the population density of the stink bugs. Finally, C. distichophylla is shown as favorable to the maintenance of the stink bug populations over the soybean and corn off-season.